Fast and direct quantification of underivatized muscone by ultra performance liquid chromatography coupled with evaporative light scattering detection. Issue 11 (27th April 2013) - Jin, Cheng; Yan, Chunxia; Luo, Yun; Li, Baocai; He, Jing; Xiao, Xiaohe
<x xml:space="preserve">Abstract</x> A new reversed phase ultra performance liquid chromatography coupled with evaporative light scattering detection is developed for the fast and direct quantification of underivatized muscone in precious herbal medicine musk. Separation of muscone was achieved on a Waters Acquity BEH C18 (50 × 2.1 mm id, 1.7 μm) column. The runtime was as short as 5 min. The mode of evaporative light scattering detection was set at Impact On. The influence of evaporative light scattering detection condition on sensitivity was investigated. The optimized condition was: drift tube temperature at 30°C, gas flow rate 4.2 L/min. The method was validated with respect to the precision, sensitivity, accuracy, linearity, stability, and robustness were measured in this paper. The calibration curves showed good linear regression (r = 0.9914) within the test range. The recovery rate was 98.6%. The limit of detection for muscone was 2.0 ng. The validated method was rapid, simple, reproducible, and convenient for the quantification of muscone in musk and the related products.